2018
DOI: 10.5812/ijp.61034
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Respiratory Syncytial Virus on the Severity of Acute Bronchiolitis in Hospitalized Infants: A Prospective Study from Turkey

Abstract: Objectives: Respiratory syncytial virus (RSV) is a major cause of respiratory infections in infants and children. The aim of this study was to evaluate clinical significance of respiratory infections as single pathogen RSV, respiratory viruses with RSV and those with bronchiolitis caused by other respiratory viruses. Methods: A total of 316 throat swabs were collected from children diagnosed with acute bronchiolitis. Real-time polymerase chain reaction was used to identify the viruses in the samples. The subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
5
5
Order By: Relevance
“…A prospective study from Turkey identified that the rate of coinfection among children with acute bronchiolitis was 34.2%, which is higher than the percentage observed in our study. 24 Similarly, a study from Israel showed that the rate of co-infectin in infants with acute bronchiolitis was nearly 40%, which is also higher than that in our study. 25 A UK study reported an even higher percentage of 46%.…”
Section: Discussioncontrasting
confidence: 59%
“…A prospective study from Turkey identified that the rate of coinfection among children with acute bronchiolitis was 34.2%, which is higher than the percentage observed in our study. 24 Similarly, a study from Israel showed that the rate of co-infectin in infants with acute bronchiolitis was nearly 40%, which is also higher than that in our study. 25 A UK study reported an even higher percentage of 46%.…”
Section: Discussioncontrasting
confidence: 59%
“…A prospective study from Turkey identified that the rate of coinfection among children with acute bronchiolitis was 34.2%, which is higher than the percentage observed in our study. 25 Similarly, a study from Israel showed that the rate of co-infectin in infants with acute bronchiolitis was nearly 40%, which is also higher than that in our study. 26 A UK study reported an even higher percentage of 46%.…”
Section: Discussioncontrasting
confidence: 59%
“…Also, RSV is more prevalent in infancy. The WHO has reported RSV as a causative pathogen for over 30 million new cases of lower respiratory infection episodes, including acute bronchitis in children less than 5 years age [52]. Older siblings are a greater source of spreading infection than adults because they spend significant time in nurseries and schools [55].…”
Section: Children Have More Trained Immunity After Previous Infections *mentioning
confidence: 99%
“…Interestingly, what have shed light on this under representation comes from two studies that revealed multiple high-titer antibodies against respiratory syncytial virus (RSV) and Mycoplasma pneumoniae (MP) in the blood of children appears to offer cross protection against SARS-CoV-2 infection [ 50 , 51 ]. Several studies have shown that children are more susceptible than adults to infection by RSV and MP [ 52 55 ]. MP has been reported in 10–40% of community-acquired pneumonia cases, and children with 5–15 years age are the most susceptible groups.…”
Section: Immunological Considerationsmentioning
confidence: 99%